Extraction and characterization of waste plastic oil (WPO) with the effect of n-butanol addition on the performance and emissions of a DI diesel engine fueled with WPO/diesel blends. (1st January 2017) - Damodharan, D.; Sathiyagnanam, A.P.; Rana, D.; Rajesh Kumar, B.; Saravanan, S.
Highlights: Waste plastic oil was extracted from mixed waste plastic by catalytic pyrolysis. n -Butanol was added up to 30% to WPO/diesel blends to form ternary blends. Engine performance and fuel consumption improved with n -butanol addition. Smoke reduced for all blends but NOx increased (except for 10% n -butanol addition). HC increased while CO remained unaffected. Abstract: With growing global energy demands, recovering energy from waste plastic presents an attractive avenue to explore as it promotes recycling. Oil synthesized from waste plastic can be excellent fuel for diesel engines but yields higher carcinogenic smoke emissions and poor performance than fossil diesel (D). This study demonstrates the extraction and characterization of waste plastic oil (WPO) obtained by pyrolysis in a laboratory scale batch reactor and later sets out to investigate the effects of adding a renewable oxygenated component in the form of n -butanol (B), a naturally occurring biofuel. Three ternary blends, D50-WPO40-B10, D50-WPO30-B20 and D50-WCO20-B30 were strategically prepared to utilize both a recycled component (WPO by up to 40%) and a renewable component ( n -butanol by up to 30%). The performance and emissions of DI diesel engine when fueled with these blends was then analyzed in comparison with both neat WPO and diesel operation. Results indicated that n -butanol addition presented lower smoke emissions and higher HC emissions when compared to diesel. Addition of 10% n -butanol by vol . to WPO/ULSD blend reduced NOx emissions favorably when compared to both WPO and diesel. However NOx emissions were higher than the corresponding WPO case for higher volume n -butanol blends. Brake thermal efficiency (BTE) of the engine increased with increasing n -butanol fraction in the blends when compared to WPO. Fuel consumption of ternary blends was found to be better than WPO. D50-WPO40-B10 blend presented less NOx and smoke emissions with improvement in engine performance when compared to diesel. Study revealed that n -butanol could be a viable additive for diesel engines operating with WPO extracted from mixed waste plastic.